(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Primavera is crucial tool for major construction projects where scheduling is required. This paper lists the activities of Pune metro rail bridge work for a 10km stretch of bridge work and highlights the enterprise project structure, organizational breakdown structure, the work breakdown structure and its activities and thus highlight the impact of Primavera P6 in the planning of projects of greater magnitude.